PENGEMBANGAN MEDIA FLIPBOOK DIGITAL MENGGUNAKAN APLIKASI HEYZINE PADA PEMBELAJARAN IPAS DI KELAS V SEKOLAH DASAR - Denisa, Salsa Billa; Astimar, Nelly (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research is motivated by the need for innovation in the world of education that utilizes technology to support learning in schools. Even though the existing facilities are sufficient to create learning media. This research aims to develop digital flipbook media using heyzine in science and science learning in class V elementary school that is valid, practical and effective. This type of research is development research (R&D) with the ADDIE model including analysis, design, development, implementation and evaluation. Data from this research were obtained from validation results, practicality questionnaires, pre-test and post-test questions. The validation sheet is filled in by material, language and media experts. Then a trial was carried out at SDN 21 Bandar Buat, Padang city by 16 people, consisting of 8 boys and 8 girls in class V. The results of this research obtained learning media in the form of digital flipbooks which were valid, practical and effective. The overall validation results obtained a percentage of 94.73% in the "Very Valid" category. The practicality results from the teacher response questionnaire were 92.85% in the "Very Practical" category and 90.36 for students in the "Very Practical" category. Meanwhile, the results of the effectiveness of the pre-test and post-test questions have increased. Thus, the use of digital flipbook media using the heyzine application in science and science learning in class V elementary school is declared valid, practical and effective in use.